Correlation Between Vitreous Level of Angiogenic Growth Factors and Oxygen Saturation in Retinal Vessels in Diabetic Retinopathy - Morin, Hana; Havlík, Jan; Chrapek, Oldrich; Hrevuš, Michal; Nemec, Pavel; Rejmont, Leoš; Tesar, Jan; Kalousova, Marta; Zima, Tomaš; Šín, Martin (Investigative ophthalmology & visual science, 2023)
PURPOSE: The aim of this study was to investigate whether there is any association between the levels of the angiogenic growth factors and the vascular oxygen saturation in eyes with diabetic retinopathy. METHODS: The study was designed as a prospective trial. The cohort consisted of 29 diabetic patients with scheduled vitreous procedures (intravitreal injection or pars plana vitrectomy). The control group included 30 patients scheduled for macular surgery (macular hole or epiretinal membrane). Nine patients (four from the diabetic maculopathy [DM] group and five from the control group) were excluded from the study because of unsuccessful vitreous samples. Retinal oximetry was performed several hours before the vitreous procedure was performed, and vitreous samples were obtained during the procedure. The concentrations of VEGF, Serpin F1/pigment epithelium-derived factor (PEDF), and placental growth factor (PlGF) were measured by ELISA. RESULTS: A negative correlation between level of VEGF and arteriovenous (AV) saturation difference was determined in the DM group (Pearson correlation coefficient r = -0.607; two-tailed test, P = 0.002). Also a negative correlation between level of PlGF and AV saturation difference was determined in the DM group (Pearson correlation coefficient r = -0.521; two-tailed test, P = 0.011) A positive correlation between PlGF level and the vein saturation was not statistically significant (Pearson correlation coefficient r = 0.325; two-tailed test, P = 0.130). We did not find any correlation between vitreous level of PEDF and vascular saturation within the DM group. CONCLUSIONS: Our findings in diabetic patients suggests a correlation between the intravitreal level of proangiogenic factors and the AV difference measured by retinal oximetry.
Keywords: retinální cévy; placentární růstový faktor; Retinal Vessels; Retina; Female; Humans; Diabetes Mellitus; Oxygen Saturation; lidé; Prospective Studies; ženské pohlaví; diabetes mellitus; Vascular Endothelial Growth Factor A; Placenta Growth Factor; vaskulární endoteliální růstový faktor A; saturace kyslíkem; prospektivní studie; Diabetic Retinopathy; retina; diabetická retinopatie